Research of Software-Hardware of Industrial Robots - J.Sh. Sodikjanov; Q.A.Khayitboyev (Zien Journals, 2023)
This article explores the research conducted on the software and hardware aspects of industrial robots. Industrial robots have become integral to the manufacturing industry, and their performance relies heavily on the integration of reliable software and hardware systems. The research on software focuses on motion planning and control, perception and sensing, human-robot interaction, and the integration of artificial intelligence and machine learning. Hardware research investigates actuation systems, sensing technologies, collaborative and mobile robotics, and power and energy efficiency. The findings from this research contribute to enhancing the capabilities, safety, and efficiency of industrial robots, paving the way for their widespread adoption in various industries.
Keywords: productivity; recognition; efficiency